(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Smart Helmet is designed to prevent most of the fatal accidents as it acts as the protective head gear for the rider. This smart helmet provides safety for the rider and also finds out the location where vehicle is located by sending the location through message in case of vehicle theft and fall detection. The Smart Helmet through belt-tie sensor detects whether the rider is wearing the helmet or not and switches the ignition ON only if the helmet is worn, otherwise it remains in OFF condition. This also follows the same condition as that of the belt-tie sensor where the ignition will not turn ON if the rider is drunk. Relay module is used as a link which communicates between the Helmet module and the Engine Control Unit (ECU). One interesting feature here is in case if vehicle theft the vehicle can be tracked by sending the message to the number present in the GSM SIM slot, and if the vehicle has met with an accident, then the Tilt sensor/MEMS in the ECU senses the Axis and message by the GSM is sent to the registered number with their current location using GPS module.